2016
DOI: 10.1002/jcp.25446
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage-Specific and Cre-Dependent Nkx3.2 Overexpression In Vivo Causes Skeletal Dwarfism by Delaying Cartilage Hypertrophy

Abstract: Nkx3.2, the vertebrate homologue of Drosophila bagpipe, has been implicated as playing a role in chondrogenic differentiation. In brief, Nkx3.2 is initially expressed in chondrocyte precursor cells and later during cartilage maturation, its expression is diminished in hypertrophic chondrocytes. In addition to Nkx3.2 expression analyses, previous studies using ex vivo chick embryo cultures and in vitro cell cultures have suggested that Nkx3.2 can suppress chondrocyte hypertrophy. However, it has never been demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 64 publications
2
7
0
Order By: Relevance
“…Limb defects have not been reported in mouse mutants (Herbrand et al, 2002;Lettice et al, 1999;Tribioli and Lufkin, 1999), but changes in the regulation of Nkx3.2 expression have been linked to tibia length (Castro et al, 2019), suggesting that the gene has a similar role in humans and mice and that the reason limb defects have not been found in mouse mutants is that the mutation is perinatally fatal, while these limb phenotypes appear postnatally (Hellemans et al, 2009). These results are consistent with a common role for Nkx3.2 in repressing chondrocyte maturation and therefore endochondral bone formation, as downregulation or gene knockout results in longer endochondral limb and median fin bones in all three species (Castro et al, 2019;Hellemans et al, 2009), and Nkx3.2 overexpression in mice causes the opposite -skeletal dwarfism (Jeong et al, 2017).…”
Section: Discussionsupporting
confidence: 64%
“…Limb defects have not been reported in mouse mutants (Herbrand et al, 2002;Lettice et al, 1999;Tribioli and Lufkin, 1999), but changes in the regulation of Nkx3.2 expression have been linked to tibia length (Castro et al, 2019), suggesting that the gene has a similar role in humans and mice and that the reason limb defects have not been found in mouse mutants is that the mutation is perinatally fatal, while these limb phenotypes appear postnatally (Hellemans et al, 2009). These results are consistent with a common role for Nkx3.2 in repressing chondrocyte maturation and therefore endochondral bone formation, as downregulation or gene knockout results in longer endochondral limb and median fin bones in all three species (Castro et al, 2019;Hellemans et al, 2009), and Nkx3.2 overexpression in mice causes the opposite -skeletal dwarfism (Jeong et al, 2017).…”
Section: Discussionsupporting
confidence: 64%
“…One of the gene regions under selection was associated with Homeobox gene NKX3-2, which is involved in skeletal development, specifically in the ossification and longitudinal growth of bone (Jeong et al 2017). Selection for genes involved in skeletal development between krill-feeding and fish feeding seal colonies could be a result of the very high levels of fluoride which are found in krill, but not in fish.…”
Section: Biological Function Of Genomic Regions Under Selectionmentioning
confidence: 99%
“…As described above, many papers, including our own work (12,13,15,17), have shown that NKX3.2 expression is associated with reduced chondrocyte hypertrophy, and thus maintenance of a healthy AC phenotype. Taking the mechanism into consideration described by Im and Kim, this would imply that under healthy cartilage conditions where NKX3.2 expression is relatively high, HIF1α would be more effectively targeted for degradation.…”
mentioning
confidence: 80%